Trapping and cooling of highly charged or radioactive ions - Kluge, Heinz-Jürgen (Nuclear physics. A, Nuclear and hadronic physics, 2000)
Ion traps and storage rings provide unique experimental conditions for the study of the properties of stable or radioactive, singly or highly charged ions. Storage of the confined particles for extended periods of times and cooling are the key issues for extremely high accuracy and sensitivity. At many accelerators such facilities are in operation or planned for experiments in atomic and nuclear physics.
Gesehen am 04.03.2020